Management of comminuted fractures of the shaft of femur by interlocking nailing at a tertiary level hospital in India - Kekatpure, Aashay; Singh, Shikhar D.; Kale, Sachin; Chaudhari, Prasad; Dhar, Sanjay (International Journal of Research in Medical Sciences, 2016)
Background: Fracture shaft of femur is one of the most common fractures encountered in orthopaedic practice. Fracture shaft of femur is major cause of morbidity and mortality in patients who sustain high energy trauma. This study looks at the epidemiology of patients presenting with femur fracture at a tertiary level hospital in Navi Mumbai. Methods: This prospective study was performed at a tertiary level hospital in Navi Mumbai from January 1, 2014 till July 31, 2015. All patients aged 18 years or above, who presented with comminuted femur fracture and were treated with interlocking nailing was included in the study. Various clinical and radiological parameters were collected during the course of treatment. Results: 50 patients were included in the study; 84% males. 88% aged 50 years or less. Road traffic accident was the most common mode of injury and 54% of patients had fracture in the middle one-third femur. 76% of the patients presented within 24 hours of injury. 52% of the patient’s demonstrated clinical union of the fracture in 12 to 14 weeks and majority showed radiological union in 16 to 18 weeks. Partial weight bearing was started in 36% patients in 10 weeks and full weight bearing in 42% patients in 16 weeks. Majority of the patients stayed in hospital for 10 to 14 days and the functional outcome as measured by Klemm and Borner criteria was excellent in 66% patients. Complications were seen only in 6 patients. Conclusions: In our experience, interlocking nailing had very low complication rate and excellent functional outcome in two thirds patients of comminuted femur fracture.